2001
DOI: 10.1002/jsfa.844
|View full text |Cite
|
Sign up to set email alerts
|

Combination of bulk storage in controlled and modified atmospheres with modified atmosphere packaging system for chilled whole gutted hake

Abstract: Whole gutted hake placed in boxes of ice were kept in modified and controlled atmospheres for 12 days with the gas mixture 60%CO2/15%O2/25%N2 (v/v/v) at 2 ± 1 °C. Each lot of hake was then subdivided into two other lots and these were packed on trays, some of them in air and some in the same mixture of gases. The trays were kept at 2 °C until spoilage. The shelf‐life of the hake stored in these conditions was assessed by physical (pH), chemical (TVBN (total volatile basic nitrogen) and TMA‐N (trimethylamine ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
2
7
0
1
Order By: Relevance
“…According to Auburg (1993), TBA values do not represent the actual lipid oxidation rate, due to several interactions between MDA and amino acids, proteins, glucose, and other fish constituents (Fernandez and others 1997) during storage. This observation is in agreement with previous reports (Fernandez and others 1997; Ruiz‐Capillas and others 2001; Pournis and others 2005; Goulas and Kontominas 2007). …”
Section: Resultssupporting
confidence: 94%
“…According to Auburg (1993), TBA values do not represent the actual lipid oxidation rate, due to several interactions between MDA and amino acids, proteins, glucose, and other fish constituents (Fernandez and others 1997) during storage. This observation is in agreement with previous reports (Fernandez and others 1997; Ruiz‐Capillas and others 2001; Pournis and others 2005; Goulas and Kontominas 2007). …”
Section: Resultssupporting
confidence: 94%
“…Although most research has been previously reported for quality changes in chilled Atlantic hake [29,43,44], studies related to its lipid fraction have been scarce and incomplete [30,31,45]. In addition, research related to the lipid fraction damage during the chilled storage of megrim [33] and angler [31] is even more scarce and incomplete.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, gas mixture 60% CO 2 /40% O 2 was found to be ideal for pearl spot. This gas mixture has also been reported to be effective in the preservation of cod fillets (Debevere and Boskou 1996) and whole gutted hake (Ruiz‐Capillas et al. 2001) where as for sole, 40% CO 2 /60% O 2 was the most effective (López‐Gálvez et al.…”
Section: Discussionmentioning
confidence: 99%
“…Product quality and shelf life in particular are important considerations in the retail and food service industries. In an effort to expand the market of high quality fresh seafood and create markets for under utilized species, modified atmospheres (MAs) have been successfully used worldwide to extend the shelf life of fresh seafood (Stammen et al 1990;Dalgaard et al 1993;Silva et al 1993;López-Gálvez et al 1995;Randell et al 1995;Reddy et al 1995;Ruiz-Capillas et al 2001). The gases and their concentration levels used in MAs must be tailored for the individual product (Reddy and Armstrong 1992).…”
Section: Introductionmentioning
confidence: 99%